2022
DOI: 10.1002/acm2.13652
|View full text |Cite
|
Sign up to set email alerts
|

Matched linac stereotactic radiotherapy: An assessment of delivery similarity and distributive patient‐specific quality assurance feasibility

Abstract: Matching multiple linacs to common baseline data allows patients to be treated, and patient‐specific quality assurance (PSQA) to be completed on any linac. Stereotactic body radiotherapy (SBRT) requires higher levels of accuracy and quality assurance than routine radiotherapy. The achieved linac matching must therefore be evaluated before distributive treatment or PSQA models can be implemented safely. This investigation aimed to propose metrics for defining linacs to be matched for SBRT deliveries, assess 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…Goodall et al have proposed an analysis to determine the feasibility of implementing a distributive PSQA approach when matched linacs are available (Goodall et al 2022). They concluded that discrepancies in linac performance translate into inconsistencies in PSQA measurements and assess the level of linac matching accuracy needed to obtain consistent PSQA results.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Goodall et al have proposed an analysis to determine the feasibility of implementing a distributive PSQA approach when matched linacs are available (Goodall et al 2022). They concluded that discrepancies in linac performance translate into inconsistencies in PSQA measurements and assess the level of linac matching accuracy needed to obtain consistent PSQA results.…”
Section: Miscellaneousmentioning
confidence: 99%
“…All linacs have previously been shown to be well matched to a single beam model within the Monaco TPS and to each other. [18] A total of 82 cranial SRS treatment plans with either single or multiple targets per isocentre, using between 3 and 6 non coplanar VMAT arcs and a 6FFF energy, were measured using a CC01 ionisation chamber in a solid water phantom. A total of 28 SBRT prostate, bone or lung plans using coplanar dual VMAT arcs and a 6FFF energy were measured using a CC04 ionisation chamber in either a solid water phantom or the CIRS thorax phantom (Sun Nuclear Corporation, Norfolk, VA, USA).…”
Section: Comparisons To Psqamentioning
confidence: 99%
“…All linacs had previously been shown to be well matched to a single beam model within the Monaco TPS and to each other. 17 A total of 82 cranial SRS treatment plans with either single or multiple targets per isocentre, using between 3 and 6 non coplanar VMAT arcs and a 6FFF energy, were measured using a cc01 ionisation chamber in a solid water phantom. A total of 28 SBRT prostate, bone or lung plans using coplanar dual VMAT arcs and a 6FFF energy were measured using a cc04 ionisation chamber in either a solid water phantom or the CIRS thorax phantom (Sun Nuclear Corporation, Norfolk, VA, USA).…”
Section: Comparisons To Psqamentioning
confidence: 99%